Prevalence and correlates of current cigarette smoking among transgender women in Argentina - Cartujano-Barrera, Francisco; Mejia, Raul M.; Radusky, Pablo D.; Cardozo, Nadir; Duarte, Mariana; Fabian, Solange; Caballero, Romina; Zalazar, Virginia; Ramos-Pibernus, Alixida; Alpert, Ash B.; Cupertino, Ana Paula; Frola, Claudia; et al. (Frontiers in Public Health, 2023)
Objective: Assess the prevalence of current cigarette smoking among transgender women in Argentina, and to examine the unique associations of current cigarette smoking with demographic and psychosocial factors. Methods: This study is a secondary data analysis of the TransCITAR - a prospective cohort study of transgender individuals living in Buenos Aires, Argentina - baseline data. Results: A total of 41.7% of participants (N=393) reported current cigarette smoking. Compared to their non-smoking counterparts, participants who reported current cigarette smoking 1) had completed less education, 2) were more likely to be born in Argentina, 3) more likely to had migrated to Buenos Aires from other parts of the country, 4) more likely to report a history of sex work, 5) more likely to perceive their health as excellent, 6) more likely to screen positive for hazardous alcohol drinking, 7) more likely to report any substance and cocaine use in the past year, 8) more likely to experience gender identity stigma from the police in the past year, and 9) more likely to being arrested in their lifetime (all p's < 0.05). After controlling for all significant associations, education level of less than high school (AOR = 1.79, 95% CI 1.02-2.12), hazardous drinking (AOR = 2.65, 95% CI 1.30-5.37), and any substance use in the last year (AOR = 2.14, 95% CI 1.16-3.94) were positively and independently associated with current cigarette smoking. Conclusion: Current cigarette smoking was associated with education, hazardous drinking, and any drug use.